Physical properties of sodium caseinate edible films and its application as coating on bread buns - Yap, Yuh Ming (2018)
Breads and buns are known to have relatively short shelf life, and staling process is the major reason for such deterioration. Packaging, which serves as a protective layer to food, is able to retard the staling process. Non-biodegradable petroleum based synthetic packaging is among the commonly used materials for food packaging due to its good mechanical, moisture, gas and aroma barrier properties. However, the rise of nonbiodegradable packaging waste in an alarming rate has led to a paradigm shift from synthetic packaging to biodegradable packaging. Therefore, various natural resources have been used for edible films and coatings development. The main purpose of the study was to establish an effective edible packaging system developed from sodium caseinate to prolong the shelf life of buns. Edible films consisted of various level of sodium caseinate (6%, 7% and 8% (w/w)), sorbitol (1:0.25, 1:0.5, and 1:0.75 (sodium caseinate: sorbitol)) and palm olein (1:0.0, 1:0.5, and 1:0.75 (sodium caseinate: palm olein)) were prepared in emulsion form and were casted on disposable petri dishes and dried in the oven for 24 hours. Dried films were kept under controlled environment for at least 48 hours before various tests. Barrier properties of films were tested according to ASTM Standard Method D3985 and ASTM Standard Method E96. For mechanical properties, it was tested based on the ASTM Standard Method D882, and film opacity was measured according to the BSI standard. Emulsion with optimum criteria was selected and applied on buns as coating. Uncoated, coated and cling film wrapped buns quality and shelf life were tested and compared. Results showed that, concentration of sodium caseinate, sorbitol and palm oil had significantly affected (p<0.05) the physical properties of the edible films. However, the concentration of sodium caseinate did not significantly affect (p>0.05) tensile strength of the film and concentration of palm oil did not significantly affect (p>0.05) elongation properties of the film. Overall, sodium caseinate edible films showed better oxygen barrier property but weaker water barrier property than cling film. However, as the content of lipid increased, there was a decrease in the water vapour permeability. For mechanical properties, cling film generally showed better tensile strength and elongation, but some of the edible films showed comparable stiffness (Young’s modulus) with cling film. Besides that, edible films without lipid showed comparable transparency with the cling film. As the protein and lipid content increased, the films showed higher opacity. However, the increased in plasticizer content, resulted in less opaque film. As for the application of coating on buns, coated buns and cling film wrapped buns had longer shelf life than uncoated buns. However, coated buns shelf life was one day shorter than cling film wrapped buns. For texture, although cling film wrapped buns and coated buns did not show better overall quality, however, due to the excellent gas barrier properties, it prolonged the buns shelf life. In conclusion, although application of coating prolonged the buns shelf life, however coated buns may become unacceptable due to the deterioration in eating quality. Therefore, modifications need to be done to improve the physical properties of the edible film.